Neurophysiological effects of exercise in the heat - Roelands, B.; De Pauw, K.; Meeusen, R. (Scandinavian Journal of Medicine & Science in Sports, 2015)
Fatigue during prolonged exercise is a multifactorial phenomenon. The complex interplay between factors originating from both the periphery and the brain will determine the onset of fatigue. In recent years, electrophysiological and imaging tools have been fine-tuned, allowing for an improved understanding of what happens in the brain. In the first part of the review, we present literature that studied the changes in electrocortical activity during and after exercise in normal and high ambient temperature. In general, exercise in a thermo-neutral environment or at light to moderate intensity increases the activity in the ß frequency range, while exercising at high intensity or in the heat reduces ß activity. In the second part, we review literature that manipulated brain neurotransmission, through either pharmacological or nutritional means, during exercise in the heat. The dominant outcomes were that manipulations changing brain dopamine concentration have the potential to delay fatigue, while the manipulation of serotonin had no effect and noradrenaline reuptake inhibition was detrimental for performance in the heat. Research on the effects of neurotransmitter manipulations on brain activity during or after exercise is scarce. The combination of brain imaging techniques with electrophysiological measures presents one of the major future challenges in exercise physiology/neurophysiology.